2006
DOI: 10.1002/hep.21325
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of peginterferon alpha-2b in chronic hepatitis delta: Relevance of quantitative RT-PCR for follow-up

Abstract: Hepatitis delta virus (HDV) can cause severe acute and chronic liver disease in patients infected by hepatitis B virus. Interferon alpha at high doses, although poorly efficient, is the only treatment reported to provide some benefit in chronic hepatitis delta. Pegylated interferon alpha (PEG-IFN) has not yet been evaluated. Treatment is usually monitored by the qualitative detection of HDV-RNA in serum. In this study, safety and efficacy of PEG-IFN were assessed in chronic hepatitis delta, and serum HDV-RNA k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
185
1
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(203 citation statements)
references
References 39 publications
7
185
1
10
Order By: Relevance
“…Although treatment is not yet satisfactory, a proportion of patients with chronic hepatitis D benefit form IFN-a treatment, There are five relatively small randomized controlled clinical trials using IFN monotherapy in patients with chronic hepatitis D with a variable dosing (from 3 to 9 MU) and different treatment periods (from 3 to 24 months) ( Table 3). The response is limited and variable depending on the different schedules of treatment [39][40][41][42][43][44][45]. Up to 70% of patients may reach a normal aminotransferase level while on treatment, but the relapse rate is high after discontinuation.…”
Section: Standard or Pegylated Ifn Monotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Although treatment is not yet satisfactory, a proportion of patients with chronic hepatitis D benefit form IFN-a treatment, There are five relatively small randomized controlled clinical trials using IFN monotherapy in patients with chronic hepatitis D with a variable dosing (from 3 to 9 MU) and different treatment periods (from 3 to 24 months) ( Table 3). The response is limited and variable depending on the different schedules of treatment [39][40][41][42][43][44][45]. Up to 70% of patients may reach a normal aminotransferase level while on treatment, but the relapse rate is high after discontinuation.…”
Section: Standard or Pegylated Ifn Monotherapymentioning
confidence: 99%
“…Improvement in clinical outcome and survival has been reported by Farci et al [44], even in patients with cirrhosis at baseline. Castelnau et al [45] recently reported a study using pegylated IFN-a-2b to treat 14 chronic hepatitis D patients for 12 months. The results disclosed that 57 and 36% of patients achieved virological and biochemical response, respectively.…”
Section: Standard or Pegylated Ifn Monotherapymentioning
confidence: 99%
“…Treatment with this type of IFN induced rates of sustained virological responses that varied from 17% to 43%4-6 However, these studies also included only a small number of patients and are difficult to compare because of the clinical heterogeneity of the patients; the highest rates of sustained virological response were reported in a series of 14 patients, most of whom did not have cirrhosis (a common complication in patients with HDV). 5 The paper by Wedemeyer and coworkers 7 provides information on what can be achieved with PEG-IFN-2a in patients infected with HBV and HDV. Wedemeyer et al compared the efficacy of PEG-IFN-2a alone versus its combination with adefovir and adefovir monotherapy.…”
mentioning
confidence: 99%
“…Moreover, we found a significant correlation between early virological response to PEG-IFN and sustained biochemical response and amelioration of necroinflammation scores of the liver. In recent reports, authors emphasized the importance of EVR in predicting the cases that may need extended treatment (4,(13)(14)(15). One of the striking factors in our study was that higher HDV RNA and HbsAg levels were associated with higher relapse rates in CDH and that the 2-year treatment was not superior to the 1-year treatment.…”
Section: Discussionmentioning
confidence: 49%